JASMERAH: PLATFORM EDUKASI SEJARAH BERBASIS WEBSITE SEBAGAI STRATEGI PENDIDIKAN KARAKTER GENERASI-Z GUNA MEWUJUDKAN MASYARAKAT MADANI - Rizky Amaliyah; Mita Lutviatiani (KRONIK : Journal of History Education and Historiography, 2022)
History education has a vital role in building the character of society. Reflected in the objectives of history subjects in Permendiknas Number 22 of 2006, history contains the values of heroism, exemplary service, nationalism, and an unyielding spirit that underlies the process of character and personality formation. However, the process of history learning in schools has not been maximally introducing character education to students. Schools prioritize students' cognitive rather than affective and psychomotor. The introduction of history at school is also limited to the school area. So the media is needed to introduce history to the broader community outside of school. In addition, changes in education in this global era should be made to suit the changing times. Therefore, the author initiated a media called JASMERAH, which is a platform for generation Z. The platform is specially designed to introduce historical figures. It is an attempt at the character-building of civil society in the global era. JASMERAH will be designed as a website. By the use of JASMERAH's website, the character-building education can be carried out interactively, inspiring and fun. The content in JASMERAH is beneficial for generation z to find out information about the history as well as character-building education that can be accessed anytime. The writing method in this paper uses the research & development (R&D) method with a 4D development model that focuses on two steps, define and design. Primary and secondary data sources with data analysis using SWOT. The prediction of the results of this program is to help solve the problem of character education through historical education to realize civil society.